2017
DOI: 10.1177/1368430217733116
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic dissimilarity predicts belonging motive frustration and reduced organizational attachment

Abstract: Some empirical studies show negative consequences of being demographically different from one's group, but the underlying psychological mechanisms are not well understood. To address this gap, we investigated the role of the belonging and distinctiveness motives in individuals' experiences of being ethnically dissimilar from their group. We propose that ethnic dissimilarity satisfies group members' need for distinctiveness whereas it frustrates members' need for belonging, and this frustration reduces their or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…For instance, employees who were racial/ethnic minorities reported lower levels of perceived discrimination at work when their supervisor shared their demographic background 42 . Conversely, racial minority students working in study groups with greater ethnic dissimilarity to themselves reported lower feelings of belonging and reduced organizational attachment 43 .…”
Section: Mainmentioning
confidence: 87%
“…For instance, employees who were racial/ethnic minorities reported lower levels of perceived discrimination at work when their supervisor shared their demographic background 42 . Conversely, racial minority students working in study groups with greater ethnic dissimilarity to themselves reported lower feelings of belonging and reduced organizational attachment 43 .…”
Section: Mainmentioning
confidence: 87%
“…Being a newcomer when other groups have thoroughly settled reduces a sense of belonging (Goodenow 1993). Further, Researchers argue that demographically dissimilar groups struggle to find appropriate biases upon which to form favourable identities which in turn reduces group identification (Chattopadhyay, George, and Lawrence 2004) and organizational attachment (Kim et al 2019).…”
Section: Attitudinal: Low Self-esteem and Low Self-confidencementioning
confidence: 99%
“…People who are similar to their group are likelier to report belonging 10 . Those who are marginalized economically, culturally, or racially tend to report lower belonging, partly because they are different from everyone else 11 . Indeed, daily group-level interactions that highlight identity differences (e.g., talking about travel, hobbies, or media) lead marginalized people, across numerous social identities, to experience identity threat and diminished belonging 12 .…”
Section: Introductionmentioning
confidence: 99%